Promoting international posture through history as content and language integrated learning (CLIL) in the Japanese context - Lockley, Thomas (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2015)
This article uses the conceptual framework of second language willingness to communicate (L2 WTC), and in particular the contributory construct of international posture (IP; Yashima, 2002), to report on a content and language integrated learning (CLIL) course taught in the Japanese university context. The research follows up an exploratory, small-scale study with a focused qualitative investigation. Due to space restrictions the current paper reports only on the key qualitative findings and attempts to build a picture of how the theme of the course, Japanese international history, affected learners’ IP, a construct that has been shown to be key to Japanese learners of English’s L2 WTC (Yashima, 2002). It is shown that after completing the course, learners felt more connected to the wider world, and as a result IP developed in varied and meaningful ways, seemingly increasing L2 WTC and stimulating critical thinking facilities both within and without the classroom
Keywords: content and language integrated learning, second language willing- ness to communicate, international posture, Japanese EFL